Pratical tips for infertility management - Malhotra, Jaideep; Goswami, Diksha; Gupta, Sahally; Malhotra Bora, Neharika; Malhotra, Keshav (India, Jaypee Brothers Medical Publishers, 2016)
Practical Tips for Infertility Management is a concise collection of tips for identifying the causes of infertility, necessary examinations, and procedures for its management. Divided into three sections, the book begins with an introduction to infertility, followed by a section which explains evaluation workup criteria with tables, charts and illustrations, as well as providing protocols for active management of infertility. The final section contains nearly 100 frequently asked questions with answers, to provide further succinct tips. With 90 colour images and illustrations in this compact book, Practical Tips for Infertility Management is a perfect day-to-day reference book for postgraduate medical students, and for practising gynaecologists, and ART and infertility practitioners. Key Points Concise, pocket-sized book of tips for infertility management Nearly 100 FAQs and answers 90 colour images and illustrations
Introduction to the Problem 2. An Approach to Infertility 3. Infertility: FAQs
Incluye contenido
Incluye índice
Keywords: INFERTILITY